State Regulations and Religious Endowments (Awqaf): Evaluating the Impact of the Waqf Amendment Bill 2025 on Minority Rights - Hassan, Imza; Dar, Showkat Hussain (Journal of Modern Islamic Studies and Civilization, 2026)
The management of religious endowments, or Awqaf, has long been a sensitive intersection of state authority and minority rights in India. The Waqf Amendment Bill 2025 represents a significant legislative shift, introducing fundamental changes to how Waqf properties are identified, registered, and administered. This research evaluates the socio-legal implications of the Bill, focusing on the expanded role of the state in supervising religious assets and the potential dilution of the "Waqf by User" concept. By analyzing the proposed inclusion of non-Muslim members in Waqf Boards and the centralization of power within District Collectors, this study assesses whether the Bill balances administrative transparency or infringes upon the constitutional guarantees provided under Articles 25 and 26. The paper argues that while modernization and the prevention of encroachment are necessary, the removal of the finality of Tribunal decisions may lead to prolonged litigation and insecurity within minority institutions. Ultimately, the impact of the Bill is evaluated against the principle of "principled distance" in secularism, questioning if the state’s regulatory reach compromises the autonomy of religious endowments and the broader landscape of minority rights in 2026.